MetÃ¡foras: Notas Sobre Su ProducciÃ³n Y Significado Cultural Y PolÃtico - Minetti, Ricardo Angel (European Scientific Journal, ESJ, 2018)
The purpose of this text is to outline the relevance of the study of metaphors as a valid political culture resource for approaching the study of culture and politics, since it puts at stake, in its configuration, symbolic materials produced by society generally historically, on diverse aspects of reality. It is therefore proposed to analyze metaphors belonging to the heritage of Argentina's and Latin America political history to illustrate and apply a "rule of interpretation" that accounts for its contents and modalities of elaboration.